THE ROLE OF MATTOANGING FARMER GROUP IN INCREASING MAIZE (Zea mays) PRODUCTION IN MASSEPE VILLAGE - Upri, Ali; Padapi, Astrini; R, Fitriani (J-PEN Borneo : Jurnal Ilmu Pertanian, 2023)
This study aims to determine the role of the Mattoanging farmer group in increasing maize production in the Massepe Village. This quantitative descriptive research uses a non-experimental approach with a survey type. The research using a questionnaire obtained an average percentage in learning classes 72.3%, in collaboration vehicles of 75.8%, and production units of 81.2%. After being analyzed using the Rank-Spearman Correlation, the correlation coefficient in the learning class was 0.678. In cooperative vehicles, it is 0.683; in production units, it is 0.654. These three values indicate a strong relationship with a positive direction. The significance value obtained from the three variables is below 0.05 (Î± = 5%). This means that H0 is rejected and H1 is accepted, which means that there is a significant relationship between the role of the Mattoanging farmer group as a learning class, a vehicle for cooperation, and a production unit in increasing maize production in Massepe Village, Tellu Limpoe District, Sidenreng Rappang Regency.